Corrosion insight of iron and bismuth added Sn–1Ag–0.5Cu lead-free solder alloy - Subri, Nor Wahida; Sarraf, Masoud; Nasiri-Tabrizi, Bahman; Ali, Bakhtiar; Sabri, Mohd Faizul Mohd; Basirun, Wan Jefrey; Sukiman, Nazatul Liana (Taylor & Francis, 2020)
The present study attempted to assess the corrosion performance of iron (Fe) and bismuth (Bi) added Sn–1Ag–0.5Cu (SAC105) lead-free solder alloy in NaCl-based solutions. Potentiodynamic polarisation measurements indicated that in acidic or alkaline solutions, corrosion potential (Ecorr) shifted to more negative (active) values and the corrosion current density (icorr) visibly increased. In a neutral pH solution, SAC105 solder alloys exhibited notable corrosion resistance owing to the stability of passive film formed on the surface of solder alloys. Potentiodynamic polarisation curves also showed that the addition of 0.05 wt% Fe and 1 wt% Bi improved the corrosion rate of SAC105 and lowered the Ecorr towards more noble value due to the reduced micro-galvanic interaction between the cathodic Ag3Sn IMCs and the anodic Sn matrix. Immersion tests revealed that the mass loss increased in the order: SAC105–Fe–2Bi > SAC105 > SAC105–Fe–1Bi. © 2019, © 2019 Institute of Materials, Minerals and Mining Published by Taylor & Francis on behalf of the Institute.